KONDISI TERUMBU KARANG PADA PERAIRAN DESA PINASUNGKULAN KECAMATAN TOMBARIRI KABUPATEN MINAHASA - Ibrahim Pakaya; Joshian N. W. Schaduw; Indri Manembu; Kakaskasen A. Roeroe; Natalie D. C. Rumampuk; Ridwan Lasabuda (Sam Ratulangi University, 2022)
This research was conducted in November 2021 in Pinasungkulan Waters, Tombariri District, Minahasa Regency using the UPT (Underwater Photos Transect) method. The purpose of this study was to determine the percentage value of hard coral cover and spatial information on the base line data on the condition of coral reefs in the waters of Pinasngkulan village. The results of this study were the percentage of hard coral at station 1 was in medium, station 2 was in the bad category, and station 3 was in the bad category, with the percentage of hard coral cover, station 1 (one) 35.07%, station 2 (two) 15.81%, station 3 (three) 7.73%, in general the condition of coral cover based on the Decree of the Minister of Environment No. 4 of 2001 coral reefs in Pinasungkulan waters are in bad condition with a percentage of 19.54% on average. Keywords: Condition of coral reefs, CPCe, Pinasungkulan Village Waters, UPT. ABSTRAK Penelitian ini dilaksanakan pada bulan November 2021 pada Perairan Pinasungkulan Kecamatan Tombariri Kabupaten Minahasa dengan menggunakan metode UPT (Underwater Photos Transect). Tujuan penelitian ini adalah untuk mengetahui nilai presentase tutupan hard coral dan informasi spasial base line data kondisi terumbu karang pada perairan desa pinasungkulan. Hasil penelitian persentase hard coral pada stasiun 1 masuk dalam kategori sedang , stasiun 2 beradadalam kategori buruk, dan stasiun 3beradadalam kategori buruk, dengan persentase tutupan hard coral, stasiun 1 (satu) 35,07% , stasiun 2 (dua) 15,81%, stasiun 3 (tiga) 7,73%,secara umum kondisi tutupan karang berdasarkan Keputusan Menteri LH No. 4 Tahun 2001 terumbu karang di Perairan Pinasungkulan berada pada kondisi buruk dengan persentase rata – rata 19,54%. Kata kunci: Kondisi terumbu karang, CPCe, Perairan Desa Pinasungkulan, UPT.